Investigating the role of octanol-enhanced safflower biodiesel and diesel fuels on combustion, performance and emissions in a direct-injected diesel engine - Akyuz, Selim; Celebi, Yahya; Aydin, Ahmet; Aydin, Huseyin (Taylor & Francis Inc, 2025)
This study evaluates the effect of octanol with biodiesel and petrodiesel, aiming to diminish fossil fuel dominance through sustainable energy substitution. Octanol was blended with safflower biodiesel (OB50) and diesel (OD50) at 50% by volume. Tests were performed in a four-cylinder direct-injected diesel engine under various loads and constant speed. Results showed that pure octanol exhibited longer combustion duration and ignition delay, while OB50 and OD50 had combustion duration similar to diesel. Increasing octanol concentration in the blend led to higher ringing intensity. The development of cylinder pressure curves and specific pressure efficiency were quite similar across all the tested fuels. Specific heat release rate efficiency indicated that effective combustion and heat output regions were achieved with pure octanol, while specific temperature efficiency increased in the early combustion stages but were lower with biodiesel addition. BTEs of OB50, OD50 and pure octanol were comparable to diesel fuel. The lowest BSFC were obtained for diesel and OC50, respectively. The average HC reductions were 17.6% for OB50 and 6.8% for OD50 compared to diesel. NOx emissions slightly decreased by 0.8% for OD50 while they increased by 5.33% for OB50 on average. However, CO emissions deteriorated for all the fuels.
Keywords: Biodiesel; Biofuel; Diesel engine; Exhaust emissions; Octanol; Performance